Conjugated polymer materials for detection and discrimination of pathogenic microorganisms: Guarantee of biosafety - Fengyan Wang; Min Ma; Huanzhang Cao; Xingxuan Chai; Ming Huang; Libing Liu (Elsevier, 2022)
Infectious disease outbreaks have seriously endangered global health owing to the scarcity of testing materials and techniques. Diversified materials and methods should be urgently developed for rapid detection and discrimination of pathogenic microorganisms. Conjugated polymer (CP) materials are macromolecular compounds comprising numerous covalently bonded luminescent units. They have excellent light-harvesting and optical signal amplification capabilities owing to the transmission of excitation energy along their backbone. In recent years, CP materials have aroused research enthusiasm in the biosensors field because of their outstanding optoelectronic properties. This brief manuscript provides an overall review of recent progress achieved in CP-based systems for pathogen sensing.